Protection and Monitoring System for LPG Leaks and Fires in Arduino-Based Rooms - Ivan Triyatno; Anton Yudhana (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
This research is a development of previous research in overcoming of LPG gas leaks that cause fires. The system is designed using the main sensor MQ-6 and DHT22 sensors which will detect the gas concentration and temperature in the room, the protection system is equipped with an exhaust as a room freshener and a buzzer as a direct warning alarm and a water pump to extinguish a fire. And all of data will be displayed on the application Blynk and will send a notification on email users by using a Wi-Fi network. This system has succeeded in detecting the concentration of LPG gas with a sensor detection distance of 1 cm to 7 cm getting an average time of 1.6 seconds and percentage of error comparison 2.52%. In normal temperature detection, the percentage error is 1.14% and normal humidity is 2.98%, As for detection of rising temperature by using of wax media, the percentage error is 1.84% and humidity 1.87%. From these tests and getting results with a small percentage value this system can already be used and runs as well.